1984
DOI: 10.2134/jeq1984.00472425001300010004x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Cycling in an Agricultural Watershed: I. Phreatic Movement

Abstract: Much of the runoff from agricultural fields in the southeastern Coastal Plain is carried to a stream channel system in a shallow phreatic aquifer. This subsurface runoff often passes through a band of riparian forest before becoming streamflow. It is hypothesized that the riparian ecosystem acts as a nutrient sink and reduces the concentrations and loads of nutrients in the shallow aquifer before the nutrients reach the stream channel. Concentrations and loads (kg/m2) of NO3‐N, NH4‐N, organic N, dissolved moly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(72 citation statements)
references
References 0 publications
2
68
0
1
Order By: Relevance
“…For instance, nutrient spiraling theory postulated that the interaction of stream water with adjacent riparian ecosystems can result in major changes in nutrient cycling and retention ( Figure 1C, Minshall et al, 1983;Naiman and Décamps, 1990;Fisher et al, 1998). Since the 1980s, it has been known that riparian ecosystems have a large capacity to retain and remove nitrogen originating from upslope, highlighting their potential to regulate the exchange of material between terrestrial and aquatic ecosystems (Lowrance et al, 1984;Peterjohn and Correll, 1984;Jacobs and Gilliam, 1985;Burt et al, 2010 for a review). The bidirectional nature of the lateral exchange of material (from the catchment to the stream and vice versa) and their unique ecological and functional characteristics make riparian corridors quintessential ecotones (Naiman and Décamps, 1990).…”
Section: Riparian Corridors Act As a Skin For River Systemsmentioning
confidence: 99%
“…For instance, nutrient spiraling theory postulated that the interaction of stream water with adjacent riparian ecosystems can result in major changes in nutrient cycling and retention ( Figure 1C, Minshall et al, 1983;Naiman and Décamps, 1990;Fisher et al, 1998). Since the 1980s, it has been known that riparian ecosystems have a large capacity to retain and remove nitrogen originating from upslope, highlighting their potential to regulate the exchange of material between terrestrial and aquatic ecosystems (Lowrance et al, 1984;Peterjohn and Correll, 1984;Jacobs and Gilliam, 1985;Burt et al, 2010 for a review). The bidirectional nature of the lateral exchange of material (from the catchment to the stream and vice versa) and their unique ecological and functional characteristics make riparian corridors quintessential ecotones (Naiman and Décamps, 1990).…”
Section: Riparian Corridors Act As a Skin For River Systemsmentioning
confidence: 99%
“…Several studies have reported on the retention of N0 3 by denitrification and plant uptake in the discharge zone (Lowrance et al, 1984;Lowrance, 1992, Haycock & Pinay, 1993 by comparing concentrations in groundwater and surface water. Lowrance et al (1983) also found a retention of base cations by plant uptake by comparing input and output.…”
Section: Introductionmentioning
confidence: 99%
“…Even in sites with a natural or seminatural buffer zone between a nitrogen source area and a surface water body, a range of 0.01-142 kgN*ha -1 *y -1 [16,19,28,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] is reported to enter the water. The uppermost extreme values of more than 20 kgN*ha -1 *y -1 [19,[50][51][52] are probably fluxes from adjacent slopes without superaquatic buffer zones.…”
Section: Landscape Factors Of Nitrogen Transportmentioning
confidence: 99%